Membongkar miskonsepsi lingkaran : telaah komprehensif pemahaman siswa sekolah menengah pertama - Apriyanti, Desi; Nugroho, Bayu Purna; Meilasari, Venty (International Journal of Progressive Mathematics Education, 2025)
Purpose: This study aims to assess students' mathematical conceptual understanding of circle geometry, stratified by high, moderate, and low proficiency levels. Design/methodology/approach: Employing a descriptive qualitative design, this research selected six subjects via purposive sampling, comprising two students from each proficiency tier (high, moderate, and low). Data collection utilized test instruments and structured interview protocols to evaluate conceptual mastery. Findings: The findings reveal that high-proficiency students satisfied four conceptual understanding indicators: object classification, procedural application, mathematical representation, and problem-solving algorithms. Conversely, moderate-ability students fulfilled only two indicators (classification and procedural application), while low-ability students demonstrated mastery of a single indicator: classifying objects based on specific properties. Practical implications: These results underscore the necessity for instructional strategies that emphasize procedural application and mathematical representation, particularly for low- and moderate-performing students, to bridge existing gaps in conceptual understanding. Originality/value: This study provides a distinct delineation of the gradation in mastering circle-related concepts across varying ability levels, serving as a foundational reference for instructional evaluation and curriculum adjustment. Purpose: Penelitian ini bertujuan untuk menganalisis tingkat pemahaman konsep matematika siswa pada materi lingkaran berdasarkan kategori kemampuan tinggi, sedang, dan rendah. Design/methodology/approach: Penelitian ini menggunakan metode deskriptif dengan pendekatan kualitatif. Subjek terdiri dari enam siswa yang dipilih melalui teknik purposive sampling, mencakup masing-masing dua siswa dari kategori kemampuan tinggi, sedang, dan rendah. Data dikumpulkan menggunakan instrumen tes dan pedoman wawancara.Findings: Hasil menunjukkan bahwa siswa berkemampuan tinggi memenuhi empat indikator (klasifikasi, prosedur, representasi, dan pemecahan masalah). Siswa berkemampuan sedang memenuhi dua indikator (klasifikasi dan prosedur), sedangkan siswa berkemampuan rendah hanya memenuhi satu indikator, yaitu mengklasifikasikan objek menurut sifat tertentu.Practical implications: Temuan ini mengimplikasikan perlunya penekanan strategi pembelajaran pada aspek penggunaan prosedur dan representasi matematis, khususnya bagi siswa dengan kemampuan sedang dan rendah untuk menutup kesenjangan pemahaman konsep. Originality/value: Studi ini memberikan pemetaan spesifik mengenai gradasi penguasaan indikator pemahaman konsep lingkaran pada berbagai tingkat kemampuan siswa sebagai dasar evaluasi pembelajaran.